Internal audit role on information asymmetry and real earnings management - Jasman Jasman; Muhammad Nuryatno Amin (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2017)
This study aims to investigate the effect of information asymmetry toward real earnings management which are moderated by quality of internal audit function. The research design is quantitative method using secondary data. The sample used in this study consisted of 116 manufacturing companies which are listed on Indonesian Stock Exchanges. Earnings management through real activities manipulation which is also called real earnings management is proxied with three patterns: cash flow from operation (CFO), production costs, and discretionary expenses. The result shows that information asymmetry has a positif and significant effect toward real earnings management in the pattern of cash flow from operation and production costs. Meanwhile, information asymmetry has no effect toward real earnings management in the pattern of discretionary expenses. This research also found that quality of internal audit has significant effect in mitigating the effect of information asymmetry toward real earnings management in the pattern of cash flow from operation and production costs. Internal audit quality does not play an important role in alleviating real earnings management in discretionary expenses pattern.